Reformas al código civil para implementar el restablecimiento por mutuo acuerdo de la sociedad conyugal, cuando exista aun vinculo matrimonial vigente - Sarmiento Noriega, Jhoanna Cecilia (2016)
In this research work we start from marriage is the foundation of the family unit, where the family is the cornerstone of society, whose function is to perpetuate through their children and their descendants; from that point of view culture if its cornerstone would disintegrate, the family ceased to have validity as such. We could say with some certainty that he who destroys marriage destroys not only the family but also society and therefore civilization. Considering the above the Constitution of the Republic of Ecuador in Article 67 states: the family is recognized in its various forms. The State shall protect the fundamental nucleus of society and shall guarantee conditions that promote the achievement of its objectives. These may be established by legal or factual bonds and are based on equal rights and opportunities for its members. Marriage is a union between a man and a woman, it was based on the free consent of the contracting persons and equal rights obligations and legal capacity. " The legislature has made the importance of marriage as a fundamental pillar of society, forcing the state to have some control over himself, control goes from point impediments in the law, forms, formalities and requirements for getting married marital status, to how to how you will monitor the dissolution of the same, either by annulment or divorce. In short I will say that marriage under the Constitution of the Republic of Ecuador, is the fundamental unit of society and is guaranteed by it, provided it is made up of legal or de facto ties and based on equal rights and opportunities for its members. From the moment of birth marriage, the couple also born conjugal partnership or goods, which is formed between the spouses by the fact of marriage, held under Ecuadorian law. 6 The conjugal partnership is formed between two people and born by reason of marriage; this heritage is composed of assets and liabilities to be divided equally between the spouses upon dissolution of society parties. At the time of ending the marriage, it ends the marital partnership, this completion is automatic, no other legal act or formality required; also this society may end even if the marriage is not dissolved and this may not be returned only upon remarriage can reset a new society. Art. 221 of the Civil Code states in its second paragraph that: "separated spouses may, at any time, by mutual agreement ask the judge to declare terminated the marital separation; It will be enough for the declaration of joint will of the parties, in writing, before the judge, who ensuring truth and freedom of the declaration; recognized after signatures, it will deliver judgment without further delay". So exposed to carefully analyze marriage, divorce, marital dissolution and restoration of the same, we can see that the State is who should protect the fundamental unit of society, the family, and with this the company of its assets, for which my theme of restoration of community property, shall take effect, provided they have not dissolved the marriage and spouses through a request to the judge that the dissolved restored without further formalities necessary, marital society, the assets they had before the dissolution; without making marriage contracts and other legal proceedings.